State-led opioid overdose prevention efforts: Challenges, solutions and lessons learned from the CDC Prevention for States Program (PfS). Issue 2 (3rd April 2021) - Underwood, Natasha; Rooks-Peck, Cherie; Ali, Nida; Wisdom, April; Costa, Olga; Robinson, Amber; Mells, Jamie; Bacon, Sarah
Abstract: Background: The Centers for Disease Control and Prevention's Prevention for States (PfS) program funded 29 state health departments to prevent opioid overdose by implementing evidence-based prevention strategies. The objectives of this analysis were to describe the scope of activities implemented across the four PfS strategies and identify implementation challenges. Methods: PfS recipients submitted annual progress reports (APRs) to state support staff at CDC from 2015 to 2017. APR data were used to calculate the number of required and optional activities implemented under each PfS strategy. APR data were qualitatively analyzed using a systematic content analysis approach to identify key implementation challenges. Results: From 2015 to 2017, PfS recipients implemented 177 activities across four strategies from 2015 to 2017. Cross-cutting implementation challenges were (1) multi-sector collaboration, (2) lack of knowledge and misperceptions about opioid used disorder (OUD) among some partners and local communities and; (3) management and access to opioid data among PfS recipients. Conclusions: PfS recipients implemented an array of prevention interventions to address the opioid overdose crisis and encountered several cross-cutting implementation challenges. Challenges and state driven solutions over the course of implementing PfS led to several lessons learned and actions that CDC enacted to continue to support and expand overdose prevention.